La Performatividad Colectiva como Arte Publico: Acción dentro de la Huelga de la Universidad de Puerto Rico - Bastida Kullick, Eden (2013)
In April 2010, the University of Puerto Rico experienced a moment of political convulsion due to a series of measures and budget cuts that the administration tried to implement. These events moved the students to demand a reason for these budget cuts. After not getting any clear or valid answers from the administration, the student body organized a series of protests that lead to an almost two-month long strike. My paper is mainly focused on the artistic manifestations that resulted from the strike. These, from our perspective, can easily ft into what is considered public art, may them be intended as such or not, because they transform the street into a place of dialogue and relationships.